Manajemen Permodalan Bank Syariah - Ilyas, Rahmat (BISNIS, 2017)
Bank Syariah is a syariah financial institution that is oriented to profit (Profit). Profit is not only for the benefit of the owner or the founder, but also very important for the development of sharia bank business. Bank as a financial institution which one of its functions is to collect public funds, must have a source to raise funds before the channel back to the community. As an intermediary institution, the first capital of a financial institution is trust, namely the trust of the parties it connects. In other words, the first capital of a financial institution is the credibility of which the customers or the public at large. While the second capital of a financial institution is professionalism, namely professionalism in managing money or deposit funds mandated to him.